2019
DOI: 10.7554/elife.48847
|View full text |Cite
|
Sign up to set email alerts
|

A single H/ACA small nucleolar RNA mediates tumor suppression downstream of oncogenic RAS

Abstract: Small nucleolar RNAs (snoRNAs) are a diverse group of non-coding RNAs that direct chemical modifications at specific residues on other RNA molecules, primarily on ribosomal RNA (rRNA). SnoRNAs are altered in several cancers; however, their role in cell homeostasis as well as in cellular transformation remains poorly explored. Here, we show that specific subsets of snoRNAs are differentially regulated during the earliest cellular response to oncogenic RASG12V expression. We describe a novel function for one H/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 78 publications
2
76
0
3
Order By: Relevance
“…For instance, a change in a single snoRNA H/ACA, SNORA24 which guides two pseudouridine, mediates tumor suppression, and ribosomes lacking SNORA24-guided  modifications have alterations in their biophysical properties. These findings highlight a role for specific snoRNAs in safeguarding the organism against oncogenic insults, and demonstrate a functional link between H/ACA snoRNAs regulated by RAS and the biophysical properties of ribosomes in cancer [87]. The altered residues observed in our study are mostly located in the functional domains H69 and PTC.…”
Section: Discussionsupporting
confidence: 67%
“…For instance, a change in a single snoRNA H/ACA, SNORA24 which guides two pseudouridine, mediates tumor suppression, and ribosomes lacking SNORA24-guided  modifications have alterations in their biophysical properties. These findings highlight a role for specific snoRNAs in safeguarding the organism against oncogenic insults, and demonstrate a functional link between H/ACA snoRNAs regulated by RAS and the biophysical properties of ribosomes in cancer [87]. The altered residues observed in our study are mostly located in the functional domains H69 and PTC.…”
Section: Discussionsupporting
confidence: 67%
“…Cui et al 151 found that tDR‐0009 and tDR‐7336 were notably upregulated in the SUM‐1315 cell lines stimulated by hypoxia; further, bioinformatic analysis indicated that these two upregulated tDRs might be involved in the chemoresistance to doxorubicin in TNBC via mediating the activation of phosphorylation of STAT3. As for other ncRNAs, such as snoRNA and snRNA, their tumour‐associated functions have been observed in multiple cancers, 152‐154 but no exact roles have been defined in TNBC, which need to be further explored in the future.…”
Section: Other Non‐coding Rnasmentioning
confidence: 99%
“…A H/ACA box RNP has been identified as playing a role in tumorigenesis by regulating translation. A recent study by McMahon and colleagues has shown the regulation of SNORA24 in human hepatocellular carcinoma and its collaboration with RAS mutation to promote cancer [27]. SNORA24 drives two pseudouridylations in the 18S rRNA at positions 609 and 863.…”
Section: Pseudouridylation (ψ) Machinery and Implications For Human Cmentioning
confidence: 99%
“…SNORA24 drives two pseudouridylations in the 18S rRNA at positions 609 and 863. Ribosomes lacking the corresponding modifications exhibited perturbations in the aminoacyl-transfer RNA (aa-tRNA) selection and altered pre-translocation ribosome complex dynamics [27].…”
Section: Pseudouridylation (ψ) Machinery and Implications For Human Cmentioning
confidence: 99%